Brain Disorders (Cerebral Palsy) And The Ability Of Academic - Faisal Rachmat (Journal of Educational Science and Technology (EST), 2017)
The purpose of this empirically is to get a clear picture of low intervensi given mild mental retardation (cerebral palsy) in children to improve their academic abilities. Research that started from Maret 2017 through may 2017, on a boy named AMR student in the Homeschooling Seto Brothers (HKS) Bintaro, Tangerang Selatan. This study used a qualitative approach with case study method. The collection of data through observation, interview and document research. The data were analyzed qualitatively. The result sducahowedan increase in academic knowledge after being given an educational intervention for 4 months. This is evidenced by the significant increase in work in class AMR, The LKS (Student Worksheet). Suggestions keep motivate students to remain willing to learn, the cooperation between teachers and parents should pay more attention to giving the effect is more significant in the progress of interventions undertaken in the school, pursued no alternations teacher.